Hasil Analisis Permasalahan Implementasi Pembelajaran IPA Kelas VI SDN Pegangsaan Dua 05 Pagi - Halimah Tussadiyah; Rissa Alivia Zahra; Sofiah Jauhara; Zulherman Zulherman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The implementation of science learning in schools has complex and varied challenges. This research aims to identify several general problems that arise in the implementation of science learning and find solutions that can increase the effectiveness of this learning. The problem of implementing science learning in class VI at SDN Pegangsaan Dua 05 this morning does not have too many challenges, because it suits the students' interests. The strategy is carried out through approaching students and conducting peer tutoring. It is hoped that this research will enable teachers in elementary schools to evaluate teaching results in class. Parental involvement in science learning is very lacking, but the role of parents in helping with the practical tools to be used is sufficient and very helpful.